2009
DOI: 10.1136/gut.2009.180711
|View full text |Cite
|
Sign up to set email alerts
|

HDAC2 mediates therapeutic resistance of pancreatic cancer cells via the BH3-only protein NOXA

Abstract: In summary, our data characterise a novel molecular mechanism that links the epigenetic regulator HDAC2 to the regulation of the pro-apoptotic BH3-only protein NOXA in PDAC. Targeting HDAC2 will therefore be a promising strategy to overcome therapeutic resistance of PDAC against chemotherapeutics that induce DNA damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
129
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 46 publications
17
129
0
2
Order By: Relevance
“…Chromatin immunoprecipitation revealed a significantly increased binding of acetylated histone H3 to the ZAG promoter (Figure 3d), suggesting an open chromatin conformation within that region. As it has been shown recently that inhibition of HDAC in Panc-1 cells abolished TGF-b1-mediated EMT (Fritsche et al, 2009;von Burstin et al, 2009) Figure 3e). The changes in CDH1 and VIM expression were also confirmed on the protein level ( Figure 3f).…”
Section: Azgp1 In Pancreatic Cancersupporting
confidence: 59%
“…Chromatin immunoprecipitation revealed a significantly increased binding of acetylated histone H3 to the ZAG promoter (Figure 3d), suggesting an open chromatin conformation within that region. As it has been shown recently that inhibition of HDAC in Panc-1 cells abolished TGF-b1-mediated EMT (Fritsche et al, 2009;von Burstin et al, 2009) Figure 3e). The changes in CDH1 and VIM expression were also confirmed on the protein level ( Figure 3f).…”
Section: Azgp1 In Pancreatic Cancersupporting
confidence: 59%
“…HDAC2 interacts with Snail to exert transcriptional repression of E-cadherin and the promotion of tumor metastasis (19,44). HDAC2 confers resistance to etoposide in pancreatic cancer cells by activating BH3-only NOXA (45). In our data, HDAC2 interacts with Snail in Malme3M R cells (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Increasing evidence has revealed that HDAC2 is often overexpressed in various types of tumors (10)(11)(12)(13)(14)(15). In addition, the ablation of HDAC2 markedly inhibits tumor growth and induces apoptosis (13,14,16), suggesting HDAC2 functions as oncogene in these tumors. Most importantly, monitoring HDAC2 expression during treatment can act as a marker for the efficacy of HDAC inhibitors (HDACis), and thus the HDAC2 level represents an independent prognostic marker in the clinic (17,18).…”
Section: Introductionmentioning
confidence: 99%